Pneumatic hydrodynamics influence transplastomic protein yields and biological responses during in vitro shoot regeneration of Nicotiana tabacum callus Implications for bioprocess routes to plant-made biopharmaceuticals - Barretto, Sherwin S (Biochemical engineering journal, 2017)
Transplastomic plants are capable of high-yield production of recombinant biopharmaceutical proteins. Plant tissue culture combines advantages of agricultural cultivation with the bioprocess consistency associated with suspension culture. Overexpression of recombinant proteins through regeneration of transplastomic Nicotiana tabacum shoots from callus tissue in RITA® temporary immersion bioreactors has been previously demonstrated. In this study we investigated the hydrodynamics of periodic pneumatic suspension of liquid medium during temporary immersion culture (4 min aeration every 8 h), and the impact on biological responses and transplastomic expression of fragment C of tetanus toxin (TetC). Biomass was grown under a range of aeration rates for 3, 20 and 40-day durations. Growth, mitochondrial activity (a viability indicator) and TetC protein yields were correlated against the hydrodynamic parameters, shear rate and energy dissipation rate (per kg of medium). A critical aeration rate of 440 ml min-1 was identified, corresponding to a shear rate of 96.7 s-1, pneumatic power input of 8.8 mW kg-1 and initial 20-day pneumatic energy dissipation of 127 J kg-1, at which significant reductions in biomass accumulation and mitochondrial activity were observed. There was an exponential decline in TetC yields with increasing aeration rates at 40 days, across the entire range of conditions tested. These observations have important implications for the optimisation and scale-up of transplastomic plant tissue culture bioprocesses for biopharmaceutical production